International Economics - Kindleberger, Charles P. (Illinois, 1960)
The book continues to be written for a two-semester course, em phasizing international trade the first term, and international finance the second. The line of division comes after Chapter 16. For single semester courses, it is recommended that Chapters 1-10 and 12 be re tained from the first three parts, and 19-21, 23, 24, 28 and 29 chosen from the rest. The two-semester course would naturally include sup plementary readings, on which bibliographical material is furnished at the end of each chapter, and possibly exercises. These would have to be rigorously circumscribed in a single-semester course.
Keywords: Internaitonal Ecomomic Relations